Combination Analysis and Switching Method of a Cascaded H-Bridge Multilevel Inverter Based on Transformers with the Different Turns Ratio for Increasing the Voltage Level - Lee, June Seok; Sim, Hyun Woo; Kim, Juyong; Lee, Kyo Beum (IEEE Transactions on Industrial Electronics, 2018)
This paper analyzes the combination in a cascaded H-bridge multilevel inverter (CHBI) based on transformers with the different turn ratios for increasing the voltage level and proposes the switching method for achieving the output voltage distribution among H-bridge cells (HBCs). The transformers used in this paper are connected to the output of the respective HBCs, and the secondary sides of all the transformers are connected in series for generating the final output voltage. Only one of the transformers, in particular, has a different turn ratio for increasing the output voltage level. In this paper, the possible turn ratio of the special transformer with a different turn ratio is discussed in detail, and a switching method based on the level-shifted switching method for the topology used in this paper is proposed. To verify the effectiveness of the proposed method, a three-phase 21-level CHBI is experimentally tested.
Keywords: Cascaded H-bridge inverters; Cascaded h-bridge multilevel inverters; Cascaded multilevel; Combination analysis; Multilevel inverter; Output voltages; Secondary-side; Switching methods; Cascaded H-bridge inverter (CHBI); cascaded multilevel; level-shifted switching method; multilevel inverter